2021
DOI: 10.1002/htj.22224
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations on the performance of a multistrut hydrogen injector in a scramjet combustor

Abstract: This study aims at investigating the effect of a multistrut-based hydrogen injector in a scramjet combustor underreacting case. The numerical analysis is carried out using two-dimensional Reynolds-averaged Navier-Stokes equations with the Shear Stress Transport k − ω turbulence model in contention to comprehend the flow physics during scramjet combustion. The three major parameters, such as the shock wave pattern, wall pressures, and static temperature across the combustor, are validated with the reported expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…[21][22][23] In the past 2 years, several studies have been performed in view of hydrogen-air mixtures. Kireeti et al 24 investigated the effect of a multistrut-based hydrogen injector to understand the heat transfer and fluid dynamics effects during scramjet combustion. It is found that the hydrogen jet pressure is directly proportional to the jet penetration rate in the lateral direction of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] In the past 2 years, several studies have been performed in view of hydrogen-air mixtures. Kireeti et al 24 investigated the effect of a multistrut-based hydrogen injector to understand the heat transfer and fluid dynamics effects during scramjet combustion. It is found that the hydrogen jet pressure is directly proportional to the jet penetration rate in the lateral direction of the flow.…”
Section: Introductionmentioning
confidence: 99%